Rectal indomethacin for the prevention of post-ERCP pancreatitis: A meta-analysis of randomized controlled trials - Shi, Na; Deng, Lihui; Altaf, Kiran; Huang, Wei; Xue, Ping; Xia, Qing (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: This meta-analysis was undertaken to evaluate the effect of rectal indomethacin in the prevention of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis. Materials and Methods: Major databases including Embase, Medline, Science Citation Index Expanded, Pubmed and the Cochrane Central Register of Controlled Trials, were searched to identify all relevant studies from January 1960 to July 2013. Randomized controlled trials (RCTs) comparing prophylactic use of rectal indomethacin versus placebo were included. Risk ratio (RR) with 95% confidence interval (CI) was calculated using fixed- or random-effect models. Results: Three studies met the inclusion criteria and were included in the final analyses. The overall incidence of post-ERCP pancreatitis (PEP) was significantly decreased by prophylactic rectal indomethacin compared with the placebo (RR=0.51; 95% CI=0.37-0.70). The pooled incidence of moderate to severe pancreatitis was also decreased by rectal indomethacin prophylaxis (RR=0.43; 95% CI=0.23-0.80). Conclusion: Rectal indomethacin can reduce the overall incidence and the severity of PEP.